Tumour necrosis factor production by monocytes from cattle infected with Trypanosoma (Duttonella) vivax and Trypanosoma (Nannomonas) congolense STI possible association with severity of anaemia associated with the disease - Sileghem, M.R.; Flynn, J.N.; Logan-Henfrey, L.L.; Ellis, J. (Wiley, 1994)
Plasma of cattle infected with Trypanosoma vivax IL2337 was analysed for the presence of bovine tumour necrosis factor (TNF) by EIA in which TNF was captured by a monoclonal antibody (MoAb BC9) and detected by a rabbit polyclonal antiserum. At week 2–3 post infection (p.i.) only a low activity was detected. Therefore, an alternative approach was used in which TNF production was measured ex vivo. Monocytes from T. vivax IL2337‐infected cattle manifested a strong TNF production which peaked around week 2½ p.i. Monocytes from pre‐infection controls did not produce significant concentrations of TNF. In contrast to the strong production of TNF by monocytes from cattle infected with T. vivax IL2337, TNF production was not detected from monocytes of cattle infected with Trypanosoma congolense ILNat 3.1. Trypanosomiasis due to these parasites differs in the degree if anaemia as indicated by packed cell volume (PCV). T. vivax IL2337 causes a severe, acute PCV fall whereas T. congolense ILNat 3.1. causes a more gradual fall in PCV.